2011
DOI: 10.1002/lt.22375
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the 2-step tuberculin skin test and the quantiFERON-TB gold in-tube test for the screening of tuberculosis infection before liver transplantation

Abstract: The ability of interferon-c release assays (IGRAs) to detect latent tuberculosis (TB) infection before liver transplantation (LT) is not well established. The aims of this study were (1) to compare the ability of the tuberculin skin test (TST) and the QuantiFERON-TB Gold In-Tube (QFT-IT) test (a whole-blood IGRA) to diagnose latent TB infections in patients awaiting LT and (2) to correlate the results with the severity of liver disease. We conducted a prospective, cross-sectional study of patients who were eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 19 publications
0
29
0
1
Order By: Relevance
“…Moreover, the TST failed to detect tuberculosis in any TR with active infection, although it was positive in >80% of patients from the general population. Some studies have suggested that interferon-γ release assays are more sensitive than the TST in transplant candidates and TRs [33][34][35][36]. Unfortunately, neither of the tests is infallible in diagnosing M. tuberculosis infection, or distinguishes between active and latent tuberculosis [13,14,19,37].…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, the TST failed to detect tuberculosis in any TR with active infection, although it was positive in >80% of patients from the general population. Some studies have suggested that interferon-γ release assays are more sensitive than the TST in transplant candidates and TRs [33][34][35][36]. Unfortunately, neither of the tests is infallible in diagnosing M. tuberculosis infection, or distinguishes between active and latent tuberculosis [13,14,19,37].…”
Section: Discussionmentioning
confidence: 98%
“…A number of significant limitations are associated with use of TSTs. Firstly, lower sensitivity for TB detection in severe liver disease is reported, with anergic responses recording falsely negative test results . Other concerns include poorer test specificity in patients with prior BCG vaccination or atypical mycobacteria, inconvenience related to requirement for two visits by specialist nurse, and less objective and standardized reporting.…”
Section: Discussionmentioning
confidence: 99%
“…A few studies on transplant candidates have shown some advantage of IGRA over TST. In a study on 95 patients in Spain awaiting liver transplant, the results of positive TST were lower with increasing Model for End-Stage Liver Disease score (18) and more advanced Child-Pugh-Turcotte Class (C versus A) of liver disease [13]. As the QFT-IT test positivity showed no association with stage of liver disease, the authors concluded that QFT-IT test is superior to TST for LTBI detection in patients with advanced liver disease.…”
Section: Key Pointsmentioning
confidence: 97%